Efektivitas Penggunaan Media Pembelajaran Interaktif Mentimeter Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa - Jilan Alfarrras (EDUTECH, 2023)
The background of this research pertains to the issue of low critical thinking abilities among students in Indonesia. The problem is associated with the lack of critical thinking skills in students' thinking methods, which is evident at SMAN 1 Cibadak where instability and inadequacy in critical thinking tend to occur during sociology lessons. This situation arises due to teachers not fully utilizing effective teaching media. The solution proposed by the researcher is the incorporation of the interactive learning media "Mentimeter" to enhance students' critical thinking abilities. Mentimeter is interactive presentation software developed to facilitate the delivery of content through interactive slides. The aim of this study is to describe and analyze the differences in critical thinking abilities after students use the interactive learning media "Mentimeter" as compared to the usual method of using Powerpoint. The research method employed is a quasi-experiment with a non-equivalent control group design. The population consists of 153 students in the 11th grade social studies class, with a sample of 77 students from two classes divided into an experimental group and a control group. Data was collected using essay-style test questions. Data analysis was conducted using independent sample t-tests. The results of the analysis indicate that the use of the interactive learning media "Mentimeter" is more effective in enhancing students' critical thinking abilities compared to using Powerpoint. This is supported by the results of pre-post tests (gains) for both the control and experimental groups